PENGARUH SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH, SISTEM PENGENDALIAN INTERN, STANDAR AKUNTANSI PEMERINTAH DAN PEMANFAATAN TEKNOLOGI TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris pada OPD di Kota Pekanbaru Tahun 2017), - Yulia Ratna Sari; R Adri Satriawan; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study are to examine and explain the effect of regional financial management information systems, internal control systems, government accounting standards and information technology utilization of the financial statements quality. The population used is the staff of Finance Department in all OPD in Pekanbaru as much as 29 OPD, the sample is limited to only the OPD which makes the Regional Finance Report. Furthermore, each of the OPD is taken 4 people consisting of the Head of Finance and 1 Treasurer and two staff, so that the sample as many as 116 people. Data analysis using multiple regression. Based on the results of the study, Regional Financial Management Information System (SIPKD), Internal Control System and Utilization of Information Technology has a significant influence on the Quality of Financial Statements of Pekanbaru. Government Accounting Standards do not have a significant influence on the Quality of Financial Statements Pekanbaru City.Keywords : SIPKD, SPI, Information Technology and Quality Report